Income Uncertainty and Household Savings in China - Liu, Kai (IMF Working Papers; Working Paper ;, 2010)
China's household saving rate has increased markedly since the mid-1990s and the age-savings profile has become U-shaped. We find that rising income uncertainty and pension reforms help explain both of these phenomena. Using a panel of Chinese households covering the period 1989-2006, we document that strong average income growth has been accompanied by a substantial increase in income uncertainty. Interestingly, the permanent variance of household income remains stable while it is the transitory variance that rises sharply. A calibration of a buffer-stock savings model indicates that rising savings rates among younger households are consistent with rising income uncertainty and higher saving rates among older households are consistent with a decline in the pension replacement ratio for those retiring after 1997. We conclude that rising income uncertainty and pension reforms can account for over half of the increase in the urban household savings rate in China since the mid-1990s as well as the U-shaped age-profile of savings.